Trait interindividual differences in the sleep physiology of healthy young adults - TUCKER, ADRIENNE M.; DINGES, DAVID F.; VAN DONGEN, HANS P. A. (Journal of sleep research, 2007)
Summary Despite decades of sleep research by means of polysomnography (PSG), systematic interindividual differences in PSG‐assessed sleep parameters have been scarcely investigated. The present study is the first to quantify interindividual variability in standard PSG‐assessed variables of sleep structure in terms of stability and robustness as well as magnitude. Twenty‐one carefully screened healthy young adults were studied continuously in a strictly controlled laboratory environment, where their PSGs were recorded for eight nights interspersed with three separate 36 h sleep deprivation periods. All PSG records were scored blind to subject and condition, using conventional criteria, and delta power in the non‐REM sleep EEG was computed for four electrode derivations. Interindividual differences in sleep variables were examined for stability and robustness, respectively, by comparing results across equivalent nights (e.g. baseline nights) and across experimentally differentiated nights (baseline nights versus recovery nights following sleep deprivation). Among 18 sleep variables analyzed, all except slow‐wave sleep (SWS) latency were found to exhibit significantly stable and robust – i.e. trait‐like – interindividual differences. This was quantified by means of intraclass correlation coefficients (ICCs), which ranged from 36% to 89% across physiologic variables, and were highest for SWS (73%) and delta power in the non‐REM sleep EEG (78–89%). The magnitude of the trait interindividual differences was considerable, consistently exceeding the magnitude of the group‐average effect on sleep structure of 36 h total sleep deprivation. Notably, for non‐REM delta power – a putative marker of sleep homeostasis – the interindividual differences were from 9.9 to 12.8 times greater than the group‐average increase following sleep deprivation relative to baseline. Physiologic sleep variables did not vary among subjects in a completely independent manner – 61.1% of their combined variance clustered in three trait dimensions, which appeared to represent sleep duration, sleep intensity, and sleep discontinuity. Any independent functional significance of these sleep physiologic phenotypes remains to be determined.